Trichobilharzia anseri n. sp. (Schistosomatidae: Digenea), a new visceral species of avian schistosomes isolated from greylag goose (Anser anser L.) in Iceland and France - Jouet, D; Kolářová, L; Patrelle, C; Ferté, H; Skírnisson, K (Infection, genetics and evolution, 2015)
Parasitological investigations carried out on birds in Iceland and France highlight the presence of four species of avian schistosomes from greylag geese (Anser anser L.): the european nasal species Trichobilharzia regenti and three visceral species, among which an unknown species isolated from blood vessels of the large intestine and liver. Morphological and molecular analyzes of different parasite stages (eggs, adults) revealed new species of Trichobilharzia genus – Trichobilharzia anseri sp. nov. Studies on host-parasite relationship under natural conditions, showed that the life-cycle includes the snail Radix balthica (syn. R. peregra) as intermediate host. The cercariae, already isolated in Iceland from two ponds of the Reykjavik capital area – the Family park and Tjörnin Lake – are the same as those isolated in 1999 by Kolářová et al. during the first study on Icelandic parasitic agents of cercarial dermatitis.
Keywords: Animals; Female; infekce červy třídy Trematoda; Trematode Infections; ženské pohlaví; Geese; Disease Vectors; Poultry Diseases; Schistosomatidae; nemoci drůbeže; Francie; Island; husy; DNA, Helminth; ovum; Phylogeny; DNA helmintů; Male; Iceland; Sequence Analysis, DNA; France; infekce přenášené vektorem; Snails; Ovum; zvířata; mužské pohlaví; sekvenční analýza DNA; fylogeneze; hlemýždi